Bioequivalence Analysis of Empagliflozin and Linagliptin in Human Plasma Using LC-MS/MS: Validation and Stability Studies (Development Engineering Conferences Center Articles Database, 2025)
This study presents a comprehensive bioequivalence analysis of Empagliflozin and Linagliptin (10/5 mg) in human plasma, utilizing a validated liquid chromatography-tandem mass spectrometry (LC-MS/MS) methodology. The method was validated according to EMEA and ICH M10 guidelines to ensure specificity, precision, accuracy, matrix effect evaluation, and stability under various conditions. Calibration curves demonstrated excellent linearity over the concentration range of 0.5–320 ng/mL for both compounds. The method's lower limit of quantification (LLOQ) was established at 0.5 ng/mL with a signal-to-noise ratio exceeding 10, confirming the sensitivity of the assay.Precision studies yielded within-run and between-run %RSD values within the acceptable limits, indicating high repeatability and reliability of the measurements. Matrix effects, assessed across six plasma sources, showed minimal interference, ensuring robustness of the results. Short-term and freeze-thaw stability assessments revealed deviations below ±10%, underscoring the suitability of the method for bioanalytical applications.Plasma samples collected from healthy volunteers were analyzed to determine pharmacokinetic parameters, supporting the bioequivalence of test and reference formulations. This validated method enables accurate quantification of Empagliflozin and Linagliptin in clinical studies and reinforces its utility for therapeutic drug monitoring and bioequivalence assessments.